The Influence of Knowledge and Perception of Educators' Attitude in Early Childhood Sex Education in Yogyakarta - Adikusuma, Melati Puspitajati; Purnama, Sigit; Sibawaihi, Sibawaihi; Aulia, Zahro; Khoirotin, Khoirotin (JOYCED: Journal of Early Childhood Education, 2025)
Early childhood sex education in Indonesia has become urgent due to rising cases of child sexual violence reported by authorities. Despite its proven role in preventing abuse and supporting healthy development, implementation remains limited, hindered by cultural taboos, lack of educator training, and insufficient institutional support. This study analyzed how early childhood educators’ knowledge and perceptions influence their attitudes toward sex education in Bantul Regency, Yogyakarta. Using a quantitative correlational approach and simple random sampling, 99 kindergarten teachers responded to an online questionnaire. Multiple linear regression showed knowledge and perception positively and significantly affected attitudes, contributing 36.1% simultaneously. However, many teachers still exhibit hesitant or unsupportive attitudes, influenced by cultural factors and lack of training and support. Limitations include the sample restricted to Bantul teachers, reliance on questionnaires without qualitative data, and focus only on knowledge and perceptions. Future research should expand geographic scope and methods, testing structured training and parental involvement programs. Educational institutions are advised to provide routine training based on local context and guidelines, while schools should engage parents and community leaders to reduce stigma and enhance effective early childhood sex education implementation.